PENGARUH EDUKASI TENTANG DIET DASH TERHADAP SKOR KESADARAN BAHAYA HIPERTENSI DI PUSKESMAS KENTEN PALEMBANG TAHUN 2023 - Yora Nopriani; Oscar Ari Wiryansyah; Sehlly Apriani (LPPM STIKes Mitra Adiguna, 2024)
Background: According to the records of the World Health Organization (WHO), one billion people in the world suffer from hypertension, two-thirds of whom are in developing countries with moderate and low incomes. We can do non-pharmacological therapy by providing education about the dash diet to the hypertension hazard awareness score. Where this dash diet emphasizes consuming high levels of potassium, calcium, and magnesium. Purpose: to determine the effect of education about the dash diet on the awareness score of the dangers of hypertension. Methods: Pre-experimental research design with a one group pre-test and post-test design carried out in one group without a control group. This research was conducted on January 30 - February 18, 2023. The population in this study were 266 patients who experienced hypertension at the Kenten Palembang Health Center. The sampling technique used purposive sampling with a sample of 38 respondents. Data collection through the pre-test provided question paper, then the intervention provided education about the hypertension hazard awareness score, then the post-test provided similar questions. Data analysis used univariate and bivariate analysis. Results: there is an effect of education about the dash diet on the awareness score of the dangers of hypertension (p value = 0.000). Suggestion: it is hoped that this can be an additional reference that can be used as an alternative action/therapy in non-communicable disease management programs, namely hypertension.